ANALISIS EFEKTIVITAS PENGGUNAAN MEDIA PEMBELAJARAN BERBASIS TEKNOLOGI DIGITAL PADA MATA PELAJARAN EKONOMI - Manek, Alfridus Mau; Butarbutar, Agustina (Journal Economic Education, Business and Accounting, 2024)
This research tries to focus on aspects of the effectiveness of using digital technology media in economics learning for high school students. Apart from that, teachers are required to be creative in making optimal use of technology in the learning process. It is hoped that this research can provide recommendations to economics teachers to assist decision making in choosing digital technology media that is most appropriate to the economic material to be taught. This research uses a qualitative research design with the type of library research sourced from national journals that are accessed in full open access which are relevant to the topic of this study. Library sources used for the last 5 years (2019-2024). There were 10 journal articles used as main data in this research which were selected and analyzed according to the aims and objectives of the research. These studies show that digital-based learning media, including Android applications, Cobasa Applications, CBI, e-books and digital comics, are generally effective and interesting for teaching economics. Although their effectiveness in improving overall performance may vary and their use needs to consider the advantages and disadvantages of each medium, adjusted to the conditions of the school environment and student character. Apart from that, it is hoped that teachers will be able to develop other economic materials into digital technology-based learning media so that economic learning can be more effective and maximally absorbed by students.